Komposisi, Struktur dan Cadangan Karbon pada Agroforestri Kopi Arabika di Kabupaten Aceh Tengah, Aceh - Maulidil Fajri; Nurheni Wijayanto; Iwan Hilwan (Universitas Teuku Umar, 2022)
Carbon stocks indicates the amount of CO2 that is absorbed and stored in plant biomass coffee, shade trees, undergrowth and litter. Objective research is to analyze the species composition and structure of vegetation and determine the amount of biomass, carbon stocks and CO2 uptake aboveground part in both types of coffee agroforestry with non-destructive methods, using allometric equation, in Central Aceh district. The location of the plot was determined by purposive sampling based on the representation of stands. The dominant value of a species in plants is calculated using the important value index (INP). The composition of agroforestry constituents consisted of 34 species, of which 15 species were found in simple agroforestry and 19 species in complex agroforestry. The horizontal structure of agroforestry consists of 5 diameter classes, with vegetation density decreasing continuously in the number of individuals. Carbon stocks agoforestri types of coffee in a simple decrease with an increase in diameter <10 cm and 10-19.99 cm and the complex agroforestry increases. The highest non-coffee carbon reserves are found at growth rates of 10-19.99 cm in simple agroforestry. The total component of the amount of biomass in simple agroforestry (159. 56 tons ha-1) is greater than the agroforestry complex (142.00 tons ha-1). Total CO2 uptake in both types of agroforestry was (520.16 tonsCO2 ha-1). Total CO2 uptake in simple agroforestry (275.22 tonsCO2 ha-1) was greater than in complex agroforestry (244.94 tonCO2 ha-1).Keywords: arabica coffee, agroforestry, carbon stocks and composition of vegetation